Construction of Environment Art Design System in Web Mode. Issue 1 (February 2020) - Yao, Jinxiu; Xie, Mingda
Abstract: With the national emphasis on environmental issues is gradually increasing, more and more experts and scholars on the environmental art design system of more and more research. The requirement of environmental art design system is getting higher and higher. Traditionally, two-dimensional images are used to describe environmental art geography, and the environmental information obtained lacks intuitiveness and interactivity. The purpose of this paper is to realize the social sharing and service of environmental art information so that the public can conveniently enjoy the risk warning service of environmental information. Starting from the framework reconstruction of system construction, this paper takes the Web framework pattern as the basic framework of system realization, and creates different entity models and terrain models in virtual environment through Creator modeling software. After collecting the original environmental data, the edge processing of the environmental data is carried out to produce the 3D environmental design system. In the process of 3D virtual reproduction of the environment, Vega driver software was used to shape the Web 3D scene of the environment, and the Marine environment module in Vega was used to realize dynamic and static environment simulation and simulation effect. The experimental results show that the display effect of the environmental art design system constructed in the Web mode is more realistic, intuitive, interactive and satisfactory.